PELATIHAN KOMUNIKASI TERAPUTIK DALAM MENINGKATKAN PENGETAHUAN CARING PADA SISWA SMK KEPERAWATAN - Pipin Nurhayati; Risa Arroyyani; Maryani; Yeni Isnaeni (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2025)
The basis of the therapeutic relationship between nurses and patients, which aims to improve health services, is caring behavior, characterized by concern, empathy, and compassion. Developing these habits early on is very important to improve nursing students' ability to provide nursing care. Several studies show that the level of caring among nursing students and college students is still low. The purpose of this training is to improve nursing students' understanding of providing appropriate care, which they can apply when interacting with patients in hospitals. The strategies used in this activity include interactive lectures, question and answer sessions, demonstrations or hands-on practice, and the giving of gifts. Class A and Class B participated in this training for two days. Pre-test and post-test knowledge assessments were administered before and after the two-hour training session. This activity involved 24 nursing students. The average knowledge of students before the training was 10.10, and the average knowledge of students after the training was 12.60, with a p-value of = 0.000. The training results showed an increase in students' understanding of therapeutic communication through lectures, question and answer sessions, and demonstrations.